Texture search engine - Soh, Eric Wei Lun. (2012)
Texture, an important element in computer graphics, is being widely used today to facilitate the visualization of complex concepts and ideas. With the enormous amount of texture images available, there is a need for an efficient way to search for and retrieve relevant texture images.